Do all firms benefit equally from downstream FDI? The moderating effect of local suppliers’ capabilities on productivity gains - Blalock, Garrick; Simon, Daniel H (Journal of International Business Studies, 2009)
Using a panel data set on Indonesian manufacturers from 1988 to 1996, this paper examines how host-country firms’ capabilities influence their propensity to benefit from downstream foreign direct investment (FDI). We estimate local suppliers’ productivity response to multinational entry in downstream industries. We find that firms with stronger production capabilities benefit less than others. In contrast, firms with greater absorptive capacity benefit more. These results are largely robust to the inclusion of firm fixed effects, industry-year and region-year fixed effects, and other controls, and indicate the importance of firm capabilities in moderating the effect of downstream FDI on productivity. Finally, we also find some evidence, though less robust, that firms with greater complementary capabilities (proxied by firm size) also benefit more from downstream FDI.